Acute Effects of Aerobic Exercise on Negative Affect and Obsessions and Compulsions in Individuals with Obsessive-Compulsive Disorder - Abrantes, Ana M. (J Affect Disord, 2018)
BACKGROUND: The acute effects of aerobic exercise on improved mood and anxiety reduction have been demonstrated across clinical and nonclinical populations. Limited work has evaluated the acute effects of aerobic exercise on negative affect, obsessions, and compulsions in patients with Obsessive Compulsive Disorder (OCD). METHOD: Fifty-five patients (64% female) with treatment-resistant OCD were randomized to either 12 weeks of aerobic exercise (AE) or health education contact (HEC) control. Participants rated negative affect (i.e., mood and anxiety), obsessions and compulsions before and after each weekly AE or HEC session. Multilevel models were constructed to evaluate the effect of intervention condition, treatment week (time), and their interaction term in terms of acute change in affect, obsession, and compulsions. RESULTS: Results reflected a main effect of condition, such that AE resulted in significantly larger increases in positive mood, and reductions in anxiety and compulsions, as compared to HEC. There was also a main effect of time in predicting acute anxiety reduction, such that linear reductions in anxiety over the course of treatment were observed. No significant effects were observed for acute changes in obsessions. LIMITATIONS: The sample was small and was limited in demographic heterogeneity. Bouts of aerobic exercise were not standardized in terms of duration and mode, which could impact affective response to exercise, and acute affective OCD effects were exclusively self-reported. DISCUSSION: The current findings may help elucidate potential mechanisms of action of exercise on OCD outcomes. In addition, these results point toward the potential of designing exercise interventions that can teach patients to utilize individual bouts of physical activity, “in-the-moment” to improve mood and reduce anxiety and compulsions.